Paradoxical Characters in Plato’s Symposium - Ališauskas, Vytautas (Literatūra, 2018)
[full article and abstract in Lithuanian; abstract in English]This article discusses the identity of Glaucon as portrayed in Plato’s Symposium and the portrayal of Apollodorus in the dialogue. The author argues that Glaucon is to be considered in the Symposium the same person as the Glaucon portrayed in The Republic (Plato’s brother). This argument is based on the intertexutal link to Rep.V 474d–476d. Apollodorus, the main narrator of the Symposium, is depicted as a follower of the proto-cynic Antisthenes. It is suggested that Apolodorus’s character is written as a literary substitute for Antisthenes.
Keywords: prologues of Plato’s dialogues; Symposium; Republic; Glaucon; Apollodorus; Antisthenes